Vector Control of Four Switch Three-Phase Inverter Fed Synchronous Reluctance Motor Drive Including Saturation and Iron Losses Effects Based Maximum Torque Control - M. K. Metwally; Mahrous Elsamman Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents a cost-effective vector control strategy for four switch three phase (FSTP) inverter fed a synchronous reluctance motor with conventional rotor (SynRM) drive. The reduction of the number of power switches from six to four improves the cost-effectiveness, volume-compactness and reliability of the three phase inverters. In this paper, a simulation model of the drive system is developed and analyzed in order to verify the effectiveness of the approach. The application of vector control to a SynRM at maximum torque control (MTC) operation is presented with emphasis on the effects of saturation and iron losses are briefly considered. A PI controller is used to process the speed error. Two independent hysteresis current controllers with a suitable hysteresis band are utilized for inverter switches signals. A simplified steady-state d-q model including saturation and iron losses is presented. Simulation results show that the drive system provides a fast speed response and good disturbance rejection capability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3366